THE ROI REVOLUTION: MOVING BEYOND VANITY METRICS TO MANAGE WHAT TRULY MATTERS - Yuliansisti; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
The digital marketing era ushered in an unprecedented volume of data, yet many organizations remain mired in measuring superficial engagement metrics that fail to correlate with business value. This study examines the critical shift from vanity metrics to a value-centric measurement framework that accurately captures marketing's contribution to financial outcomes. The objective is to identify the key components, implementation challenges, and organizational impacts of a true Return on Investment (ROI) management system. Employing a mixed-methods approach, the research analyzed financial and marketing data from 12 companies alongside in-depth interviews with 30 CFOs, CMOs, and marketing analysts. The results reveal that companies implementing value-based metrics achieved a 28% improvement in marketing efficiency and stronger alignment between marketing and finance. The discussion centers on the evolution from last-click attribution to unified measurement models, the cultural shift required to deprioritize vanity metrics, and the role of predictive analytics. It is concluded that a revolution in marketing measurement is essential, moving beyond clicks and likes to manage metrics that directly influence customer lifetime value and profit, thereby securing marketing's strategic role.